Legal protection of personal data security in Indonesian Local Government apps: Al Farabi's perspective - Sheila Kusuma Wardani Amnesti; Siti Zulaichah; Nurul Istiqomah (Faculty of Law, University of Muhammadiyah Malang, 2025)
The rapid advancement of technology is a double-edged sword. While it provides easy access to information, it also opens the door to unrestricted access, including personal data. Governments worldwide are leveraging technology to enhance their connection with citizens and deliver top-tier public services. In this vein, the Provincial Government of DKI Jakarta as an Indonesian local government, launched a SuperApps called JAKI in 2019 as a dynamic platform for two-way communication between DKI Jakarta residents and local authorities. This research employs empirical juridical methods, incorporating statutory and conceptual approaches. Drawing from primary sources, including DKI Jakarta Regional Secretariat Decree Number 99 of 2022 concerning the Citizen Relations Management application and interviews with the Smart City Developer Service Unit, the study demonstrates that JAKI ensures robust data security. The app complies with ISO 2700, an international standard that regulates information security management systems and fulfils the three core components: confidentiality, integrity and availability. Furthermore, in alignment with Al Farabi's concept of information security accountability, the emphasis is placed on collaborative social responsibility between data owners and collectors, represented by DKI Jakarta Provincial Government. This cooperation is both fair and beneficial, adhering to the fundamental principles of political philosophy and ethics.